Comparison of the Efficacy of Inositol-Containing Medication Only versus Metformin and Inositol among Libyan Infertile Women with Polycystic Ovarian Syndrome (Razi Medical Journal, 2025)
The polycystic ovarian syndrome (PCOS) is a common endocrinological disorder among females of reproductive age worldwide. The management of PCOs included lifestyle modification, medication, and surgical treatment. This study was conducted to compare the efficacy of inositol-containing medication only versus metformin and inositol among Libyan infertile women with polycystic ovarian syndrome. This study was a randomized controlled trial that enrolled patients at the Infertility Treatment Center in Tripoli, Libya, between January and December 2024. The target sample consisted of 41 Libyan infertile women diagnosed with polycystic ovarian syndrome, who were divided into two groups: 21 patients had received inositol only, while 20 patients had received inositol combined with metformin. All statistical analysis was done using the SPSS Version 21 program. In this study, nearly half of the patients ranged between 25 and 29 years, accounting for 48.8%. Most of them were obese, with an overall percentage was 80.4%. About 22.0% had regular menstrual cycles and 58.5% had hirsutism. 61.0% of patients had primary infertility, while 39.0% of them had secondary infertility. On comparison between two groups in the study a statistically significant results and parameters improvement were reported in most of the hormonal and metabolic determinants in terms of LH, E2, AMH, HbA1C levels in both groups, with additional efficacy in HOMA-IR level for the combined group, but insignificant findings in FSH and prolactin levels. While the opposite finding had found that the inositol-only group had statistically significant results for TSH level. In summary, this study suggested that the combination of inositol treatment with metformin had significant effectiveness and parameter improvement on most of the hormonal and metabolic levels for infertile women with polycystic ovarian syndrome. Therefore, the combination of inositol and metformin therapies appears to offer additional benefits and positive results for optimization of hormonal and metabolic parameters among polycystic ovarian syndrome cases, particularly who seeking fertility advice and expressing obesity.
Keywords: Polycystic Ovarian Syndrome, PCOS, Inositol, Metformin, Libya